Effectiveness of curcumin against Enterococcus faecalis biofilm. (1st November 2013) - Neelakantan, Prasanna; Subbarao, Chandana; Sharma, Subash; Subbarao, Chandragiri Venkata; Garcia-Godoy, Franklin; Gutmann, James L
Abstract: Objectives. To evaluate the antimicrobial efficacy of curcumin against Enterococcus faecalis bioﬁlm formed on tooth substrate in vitro. Sodium hypochlorite (NaOCl) and chlorhexidine (CHX) served as standards for comparison. Materials and methods. Biofilms of E.faecalis were formed on instrumented, extracted human teeth ( n = 96). At the end of the 2nd day, 2nd and 8th weeks, specimens were treated for 30 min with one of the test solutions or saline (control) and the surviving colony-forming units (CFU/mL) was recorded. Results were analyzed by Kruskal-Wallis test and Dunnet test for pair-wise comparison with Bonferroni correction ( p = 0.05). Results. Only NaOCl showed complete eradication of bacteria at all time periods. In the 2-day and 2nd week biofilms, curcumin and NaOCl showed complete inhibition, which was significantly lower than the CFU recovered in the CHX and saline groups ( p < 0.05). In 8 week biofilms, samples treated with curcumin showed 553 ± 137.6 CFU/mL, which was significantly higher than NaOCl (0 CFU/mL), but significantly lower than CHX (2551 ± 129.8) and saline control (1.42 × 1011 ± 2.12 × 1010; p < 0.05). Conclusions. Sodium hypochlorite (3%) showed maximum antibacterial activity against E.faecalis bioﬁlm formed on the tooth substrate, followed by curcumin and CHX. Considering the potential for undesirable properties of NaOCl, the use of herbal alternatives in endodontics might prove to be advantageous.